Review of openings with shading devices at naturally ventilated buildings - Mohammad Yusoff, Wardah Fatimah; Shaharil, Muhammad Ihsan; Mohamed, Mohd Farid; Mohammad Rasani, Mohammad Rasidi; Sapian, Abdul Razak; Dahlan, Nur Dalilah (Taylor and Francis Group, 2022)
A shading device is integrated into a building in reducing the indoor solar heat gained. However, the incorporation of a shading device into an opening provides certain effects on indoor natural ventilation. Its performance in enhancing the indoor airflow is still arguable. For this reason, a comprehensive review was executed to identify the effects of a shading device on the natural ventilation of a building. A schematic review process was executed to identify the published articles that were related to the shading devices at the building openings. Subsequently, 25 articles have examined the shading devices at the building openings. The output parameters that were discussed including, the solar heat gained, temperature, energy consumption, daylighting, air quality, airflow, and thermal comfort. The studies agree that the shading device has certain effects on indoor airflow. The effects can be either good or detrimental, depending on the climatic condition, geographical location, building orientation, opening configuration, the shading function, and configuration. It is hoped that this review encourages more investigations of the combined effects of the shading device on solar radiation and natural ventilation. The combined effects are essential in achieving optimum performance of a shading device, which can reduce the solar radiation penetration and enhance the indoor natural ventilation.